Photoperiodic time measurement in insects - Dolezel, David (Current opinion in insect science, 2015)
The ratio of day-to-night length, known as the photoperiod, is used by many organisms to predict the oncoming of adverse seasons through the use of a photoperiodic clock system. The molecular and neural architecture of these time-measuring devices is unclear, although some evidence suggests involvement of circadian factors, that is, proteins responsible for daily oscillations. This review summarizes specific difficulties in the research of photoperiodic clocks, highlights recent successful studies, and suggests possible future directions available with emerging technologies.